Patient-Centered Care and Psychiatric Rehabilitation: What’s the Connection? - Hensley, Melissa A. (International Journal of Psychosocial Rehabilitation, 2013)
Why should psychiatric rehabilitation practitioners take notice of the idea of patient-centered care? After all, it seems to be updated language describing the same old medical model of care provision, with the physician in charge and everyone else, including the patient, following in lock-step behind. Leplege et al. (2007) have noted that psychiatric rehabilitation practitioners have studiously avoided use of the term “patient-centered care.” This may be because of the fact that patient-centered care does in some ways seem to keep the doctor in charge, despite rhetoric about enabling and empowering patients. The literature describing and advocating for the use of patient-centered care has been dominated by physicians and others working in medical settings, who refer to consumers of health care as “patients” and seem to keep control of health care processes in the hands of doctors. We in community mental health may see ourselves as better than that—we put our ideas about em- powerment into practice, instead of just talking about them, right?